D-branes from matrix factorizations: string theory and fundamental forces = D-branes from matrix factorizations : théorie des cordes et forces fondamentales - Hori, Kentaro; Walcher, Johannes (Comptes rendus physique, 2004)
B-type D-branes can be obtained from matrix factorizations of the Landau-Ginzburg superpotential. We here review this promising approach to learning about the spacetime superpotential of Calabi-Yau compactifications. We discuss the grading of the D-branes, and present applications in two examples: the two-dimensional torus, and the quintic. To cite this article: K. Hori, J. Walcher, C. R. Physique 5 (2004).Résumé Les D-branes de type B peuvent être décrites à partir de factorisations matricielles du super-potentiel de Landau-Ginzburg. On revoit ici cette approche prometteuse pour étudier le super-potentiel en espace-temps de compactifications de Calabi-Yau. On discute la graduation des D-branes, et présente deux exemples : le tore en deux dimensions, ainsi que la quintique. Pour citer cet article : K. Hori, J. Walcher, C. R. Physique 5 (2004).